Prediction of placebo responses: a systematic review of the literature - Horing, Bjoern; Weimer, Katja; Muth, Eric R.; Enck, Paul (Frontiers in Psychology, 2014)
Objective: Predicting who responds to placebo treatment – and under which circumstances – has been a question of interest and investigation for generations. However, the literature is disparate and inconclusive. This review aims to identify publications that provide high quality data on the topic of placebo response (PR) prediction. Methods: To identify studies concerned with PR prediction, independent searches were performed in an expert database (for all symptom modalities) and in PubMed (for pain only). Articles were selected when a) they assessed putative predictors prior to placebo treatment and b) an adequate control group was included when the association of predictors and PRs were analyzed. Results: Twenty-one studies were identified, most with pain as dependent variable. Most predictors of PRs were psychological constructs related to actions, expected outcomes and the emotional valence attached to these events (goal-seeking, self-efficacy/-esteem, locus of control, optimism). Other predictors involved behavioural control (desire for control, eating restraint), personality variables (fun seeking, sensation seeking, neuroticism), biological markers (sex, a single nucleotide polymorphism related to dopamine metabolism). Finally, suggestibility and beliefs in expectation biases, body consciousness and baseline symptom severity were found to be predictive. Conclusions: While results are heterogeneous, some congruence of predictors can be identified. PRs mainly appear to be moderated by expectations of how the symptom might change after treatment, or the expectation of how symptom repetition can be coped with. It is suggested to include the listed constructs in future research. Furthermore, a closer look at variables moderating symptom change in control groups seems warranted.